ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN EDUCATION - Nilufar Khalikova Mirkadyrovna (American Journals Publishing, 2024)
The introduction of artificial intelligence technologies in the field of education is playing an important role in improving the quality of education, providing an individual approach and optimizing educational processes. This article examines the use of artificial intelligence technologies in education, including adaptive learning systems, virtual teachers, automated assessment systems, and learning analytics tools. Advantages, opportunities and limitations of these technologies are also considered. The integration of artificial intelligence into the educational process opens up new opportunities for teachers and helps to create an educational system adapted to the individual needs of students.
Keywords: Automated assessment, Optimization of educational processes, Analysis of educational materials, Virtual teachers, Chatbots in education, Adaptive learning systems, Data analysis, Educational efficiency, Innovative death educational programs, Smart educational platforms, Interactive educational tools, Cognitive analysis, Immersive technologies (VR and AR), Personalization in education, Intelligent learning environments